Development of a technique for real-time leakage detection and location in water distribution networks - Aburawe, Salah Muamer (2014)
Most water utilities worldwide suffer from the problem of water loss which effects the financial, social and environmental concerns. Leakage in water distribution networks is a significant issue that costs a lot, which is further complicated by the problem that the location of the leakage is usually hidden underground. The aim of this research was to develop a technique for real-time leakage detection and location in water distribution networks with acceptable accuracy, able to identify its location in the field quickly, and with reasonable cost thus encouraging its wider application. Currently acoustic methods are commonly deployed, which requires long time to perform, in addition to the high-cost resulting from the expensive devices and expenses of the field survey itself. There are also some analytical methods that rely on hydraulic analysis concept to detect the leakage. However they are unable to determine the location of leakage accurately, as they just identify a group of hot spots that are likely to be the location of leakage, and require to return to the field to find the location of the leakage. The analytical methods that rely mainly on the hydraulic modeling of the network have contributed to reducing the time needed to locate the leakage thus reducing some fraction of the cost. A combination of hydraulic analysis methods with geospatial technology should provide additional advantages. This research was conducted to develop an analytical technique to locate the leakage without the need to conduct a detailed field survey. It was done through a set of hydraulic analysis scenarios using pressure and flow field data at specific points in the network obtained in real-time using SCADA system. The development was conducted through three main stages. The proposed technique was evaluated theoretically before conducting any costly practical activity. The practical stage was accomplished in two phases, the first phase was a laboratory study to identify the hydraulic behaviour of the network before, during and after the leakage. The second phase was a field work conducted using a real water network as a case study located in Shah Alam, Selangor, Malaysia. A group of fabricated leaks were placed at specific locations in the network, and the associated pressure changes at certain observation points were monitored. A study of the results obtained from the practical stage using a calibrated model was done in the application and validation stage. A series of hydraulic analysis scenarios were applied on the hydraulic model in order to locate the leaks which had been fabricated in the field. It was found that the results were affected by the level of model calibration, where six leak locations were detected out of nine leak locations fabricated in the field. This result shows the possibility of using the developed technique to locate the leak In the case of the availability of sufficient field data to build a high calibrated hydraulic model.